Layoff Costs and Learning about Employer Financial Distress - Andreas Ravndal Kostøl; Matthew C. Merkle; Morten Grindaker (Institute of Labor Economics (IZA), 2024)
While many employees risk losing their job and having their career disrupted due to employers' financial distress, it is widely recognized that many leave their employer in anticipation of layoff. In this paper, we assess how employee costs of financial distress depend on employees learning and acting on future layoff risk. To this end, we use random assignment of bankruptcy judges as an instrument for employer shutdown and administrative data on petition and quit dates to examine how earnings costs are shaped by employee reallocation. We show that shutdown causes a 24% fall in earnings over a five-year period despite one-quarter of employees having already left their firm. We document substantial heterogeneity in reallocation and earnings losses, typically displaying an inverse relationship, with higher reallocation in strong labor markets and from high-wage firms. The reallocation attenuates earnings losses by about 50%, approximately equal to the insurance from taxes and transfers. To assess the value of information, we estimate a model where risk averse workers learn about distress, search for jobs and access public insurance. Using the model, we calculate that employees' willingness to pay for their current job increases by 14% when the firm is liquidated without any advance information. Our findings suggest that making firms' financial risk information more accessible to employees can yield important benefits.
Keywords: J62; J63; J65; J68; G33; G51; G52; 330; job loss; search; occupational choice; bankruptcy; unemployment insurance